Same-sex marriage in Latin America : promise and resistance - Pierceson, Jason, 1972-; Piatti-Crocker, Adriana, 1963-; Schulenberg, Shawn, 1979- (Lexington Books, 2013)
This volume sheds light on regional, national, and individual-level factors that have led to major developments for same-sex relationship equality in Latin America and explores institutional, political, and social barriers for same-sex couples in the region. It analyzes cross-national patterns of same-sex relationship policies in Latin America and examines country-cases of recent policies for same sex-couples in the region.